Parallelization of a two-dimensional time-area watershed routing. (December 2021) - Her, Younggu; Yang, Kwangsoo; Song, Jung-Hun
Abstract: Grid-based spatially distributed hydrological modeling has become feasible with advances in watershed routing schemes, remote sensing technology, and computing resources. However, the need for long-running times on a substantial set of computational resources prevents a spatially detailed modeling program from being widely used, particularly in fine-resolution large-scale studies. Parallelizing computational tasks successfully mitigate this difficulty. We propose a novel way to improve the simulation efficiency of direct runoff transport processes by grouping watershed areas based on a time-area routing scheme. The proposed parallelization method was applied to simulating the runoff routing processes of two watersheds in different sizes and landscapes. The method substantially improved the computational efficiency of the time-area routing simulation with common computing resources. The efficiency of the parallelization was not limited by the hierarchical relationship between upstream and downstream catchments along the flow paths, which could be possible with the Lagrangian tracking of the time-area routing method. Highlights: This study proposed a way to parallelize a grid-based time-area routing simulation. The method was applied to two watersheds having different sizes and landscapes. Lagrangian tracking made routing independent at the individual grid cell level. The parallelization method substantially sped up the time-area routing simulation. Efficiency was a function of watershed features as well as computing resources.